Open Source for Knowledge and Learning Management : Strategies Beyond Tools - Lytras, Miltiadis D., 1973-, editor 294723; Naeve, Ambjorn, editor 294731; Gale Group (Online service) 651863 (Hershey : Idea Group Pub., 2007)
Open Source for Knowledge and Learning Management: Strategies Beyond Tools explains an intense orientation to the critical issues of the open source paradigm: open source tools, applications, social networks, and knowledge sharing in open source communities. Open source technologies, tools, and applications are analyzed in the context of knowledge and learning, and this convergence formulates a challenging landscape for the deployment of information technology.